2020
DOI: 10.1213/ane.0000000000004416
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Postoperative Body Temperature and All-Cause Mortality After Off-Pump Coronary Artery Bypass Graft Surgery: A Retrospective Observational Study

Abstract: BACKGROUND: Inadvertent perioperative hypothermia is common in patients undergoing off-pump coronary artery bypass grafting (OPCAB). We investigated the association between early postoperative body temperature and all-cause mortality in patients undergoing OPCAB. METHODS: We reviewed the electronic medical records of 1714 patients who underwent OPCAB (median duration of follow-up, 47 months). Patients were divided into 4 groups based on body temperature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 31 publications
0
3
0
Order By: Relevance
“…According to DeFoe et al [ 14 ], regardless of any sites of core body temperature (nasopharyngeal, esophageal, bladder or rectal), patients undergoing isolated on-pump coronary artery bypass grafting (CABG) surgery have consistently higher in-hospital mortality rates with increasing colder temperatures; moreover, lower temperature groups were found to exhibit greater myocardial injury as assessed by myocardial markers. Likewise, Nam et al [ 20 ] reported that the all-cause mortality of moderate-to-severe hypothermia was more than two times of that in normothermia for off-pump CABG patients and even mild hypothermia (no less than 35.5℃) was found an unsatisfied outcome during the follow-up of 47 months. However, another study that enrolled isolated off-pump CABG patients showed no statistically difference for in-hospital mortality between hypothermia group and normothermia group neither before nor after propensity score matching, while a distinction in postoperative transfusion of red cell concentrates, duration of intubation and ICU stay [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to DeFoe et al [ 14 ], regardless of any sites of core body temperature (nasopharyngeal, esophageal, bladder or rectal), patients undergoing isolated on-pump coronary artery bypass grafting (CABG) surgery have consistently higher in-hospital mortality rates with increasing colder temperatures; moreover, lower temperature groups were found to exhibit greater myocardial injury as assessed by myocardial markers. Likewise, Nam et al [ 20 ] reported that the all-cause mortality of moderate-to-severe hypothermia was more than two times of that in normothermia for off-pump CABG patients and even mild hypothermia (no less than 35.5℃) was found an unsatisfied outcome during the follow-up of 47 months. However, another study that enrolled isolated off-pump CABG patients showed no statistically difference for in-hospital mortality between hypothermia group and normothermia group neither before nor after propensity score matching, while a distinction in postoperative transfusion of red cell concentrates, duration of intubation and ICU stay [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…We enrolled 8577 ICU patients diagnosed with coronary heart disease (CHD) based on the International Classification of Diseases (ICD)-10 codes from I20 to I25. Patients with censored body temperature records had been excluded, and the overall study population was divided into three groups in accordance with the prior investigation [ 20 ] and the distribution of body temperature a priori.…”
Section: Methodsmentioning
confidence: 99%
“…After removing the duplicates, we calculated the average BT of each individual using the Excel tool. We divided the patients into three groups based on the temperature performance and the existing research ( 17 20 ): hypothermia (BT <36.5°C), normal (36.5°C ≤ BT <37.5°C), and hyperthermia (BT ≥37.5°C). We obtained the survival information for the last outcome variable from the table named “patients.” From the table named “admissions,” we obtained the data regarding the length of hospital and ICU stays ( 21 ).…”
Section: Methodsmentioning
confidence: 99%